How to write and publish a scientific paper - Day, Robert A., 1924-; Gastel, Barbara, 1952- (Greenwood, 2011)
"This newly updated version of the classic guide to writing and publishing scientific papers provides the tools needed to succeed in the communication aspects of a scientific career"--Resumé vydavatele
Keywords: vědecké práce; vědecké publikace; publikační činnost; odborný styl; odborné texty; scientific reports; scientific publications; publication activity; professional style; professional texts; příručky; handbooks, manuals, etc